Antifungal, insecticidal, and plant growth promoting potential of Streptomyces hydrogenans DH16. (14th June 2013) - Kaur, Talwinder; Manhas, Rajesh Kumari
<x xml:space="preserve">Abstract</x> In the present study, an actinobacterium strain, possessing antagonistic activity against different fungal phytopathogens viz. Colletotrichum acutatum, Cladosporium herbarum, Alternaria brassicicola, Exserohilum sp., Alternaria mali, Colletotrichum gleospoiroides, Alternaria alternata, Cercospora sp., Fusarium oxysporum f.sp. dianthi and Fusarium moniliformae, was isolated from soil and identified as Streptomyces hydrogenans DH16. Application of culture supernatant (5%)/cells (107 cfu ml−1), 2 h post inoculation with A. brassicicola (105 spores ml−1), resulted in 85.95 and 93.75% suppression of black leaf spot of Raphanus sativus, respectively on detached leaves. Whereas cells/culture supernatant (above 5%) completely suppressed the disease incidence when co inoculated with fungal pathogen. The crude extract containing antifungal components was completely stable at 70 °C for 1 h retaining 90 and 67.67% activity after boiling (for 1 h) and autoclaving (121 °C for 30 min), respectively. No loss in activity was observed when treated with proteinase K and on exposure to sun and UV light and found to be active over a wide range of pH (2 to 14). Bioautography of the solvent extract against test phytopathogens revealed the presence of three active components. Ethyl acetate extract of DH16 also demonstrated insecticidal activity against Spodoptera litura, causing 40% larval mortality and extension of larval period. In addition, it produced 30 µg ml−1 of Indole Acetic Acid (IAA) in a medium containing tryptophan which promoted lateral root formation in Vigna radiata (green gram). These results indicate that Streptomyces hydrogenans holds the potential to be used as antifungal, insecticidal, and plant growth promoting agent.